Agricultural Communication Students Perceptions, Knowledge, and Identified Sources of Information About Agritourism - Katie Amaral; Leslie D. Edgar; Donald M. Johnson (Journal of Applied Communications, 2012)
With the struggling economy, agriculturalists are seeking new ways to become economically stable and viable. Agritourism is a topic that has not yet been evaluated at the collegiate level. Yet it may be an answer for agriculturalists seeking new approaches to profitability. The purpose of this study was to determine the perceptions, knowledge, and sources of information of agricultural communications students at the collegiate level in order to strengthen agritourism marketing competencies and skill development in postsecondary education. This quantitative descriptive study assessed agricultural communications students (N = 66) from 11 universities across the nation to determine students perceptions, knowledge, and identified sources of information regarding agritourism. The study maintained an 80.5% response rate. Most respondents were female (81.0%), and the majority of respondents were majoring or double majoring in agricultural communications (94%). Al most all respondents had families involved in agriculture (95.2%). Respondents ranked agriculture (M = 4.98, SD = 0.12) and agritourism (M = 4.45, SD = 0.66) as important. Agriculture-related festival(s) or event(s) (M = 4.46, SD = 0.75) were noted as the most important agritourism venue. Generally, respondents had previously attended an agritourism event (61.5%). Website (95.4%), print advertisement(s) (93.8%), and word-of-mouth (81.5%) were identified as the best sources of information in promoting agritourism. Over half of the respondents indicated not knowing whether or not their state had an agritourism department (52.3%). Future studies involving non-agricultural students’ perceptions and knowledge of agritourism must be conducted. Efforts should be made to increase agritourism marketing education and training in postsecondary education.
Keywords: agritourism; agriculture; agricultural communications; rural tourism; students’ perceptions